Factors contributing to the level of awareness amongst muslim towards concept of saving Takaful in Melaka / Ummu Khadijah Abdul Rauf - Abdul Rauf, Ummu Khadijah (2011)
Takaful or Islamic insurance is part of well growth Islamic finance industry today. The government and the industry player have done many efforts, however the small participation from the society is always doubted. Thus the variable factors will influenced level of awareness toward Saving Takaful. Due to this problem, Takaful Company should identify which factors that can best fit with level of awareness amongst Muslim toward Concept Saving Takaful. The main purpose of this study is to examine and gain a better solution of the significant relationship between factors that contributing level of awareness towards Saving Takaful. There are several factors that influencing level of awareness toward Concept of Saving Takaful, which include level of knowledge, perception and promotion. Results of the present study showed that the most influential factors of level of awareness amongst Muslim toward Saving Takaful are promotion. At the end of this study, the researcher come out with several recommendations in order to give clear vision for Takaful company to increase level of awareness amongst Muslim toward Concept Saving Takaful and will give positive perception towards Muslim with Takaful.